A Pex7 Deficient Mouse Series Correlates Biochemical and Neurobehavioral Markers to Genotype Severity—Implications for the Disease Spectrum of Rhizomelic Chondrodysplasia Punctata Type 1 - Fallatah, Wedad; Cui, Wei; Di Pietro, Erminia; Carter, Grace T.; Pounder, Brittany; Dorninger, Fabian; Pifl, Christian; Moser, Ann B.; Berger, Johannes; Braverman, Nancy E. (Frontiers in Cell and Developmental Biology, 2022)
Rhizomelic chondrodysplasia punctata type 1 (RCDP1) is a peroxisome biogenesis disorder caused by defects in PEX7 leading to impairment in plasmalogen (Pls) biosynthesis and phytanic acid (PA) oxidation. Pls deficiency is the main pathogenic factor that determines the severity of RCDP. Severe (classic) RCDP patients have negligible Pls levels, congenital cataracts, skeletal dysplasia, growth and neurodevelopmental deficits, and cerebral hypomyelination and cerebellar atrophy on brain MRI. Individuals with milder or nonclassic RCDP have higher Pls levels, better growth and cognitive outcomes. To better understand the pathophysiology of RCDP disorders, we generated an allelic series of Pex7 mice either homozygous for the hypomorphic allele, compound heterozygous for the hypomorphic and null alleles or homozygous for the null allele. Pex7 transcript and protein were almost undetectable in the hypomorphic model, and negligible in the compound heterozygous and null mice. Pex7 deficient mice showed a graded reduction in Pls and increases in C26:0-LPC and PA in plasma and brain according to genotype. The neuropathological evaluation showed significant loss of cerebellar Purkinje cells over time and a decrease in brain myelin basic protein (MBP) content in Pex7 deficient models, with more severe effects correlating with Pex7 genotype. All Pex7 deficient mice exhibited a hyperactive behavior in the open field environment. Brain neurotransmitters analysis of Pex7 deficient mice showed a significant reduction in levels of dopamine, norepinephrine, serotonin and GABA. Also, a significant correlation was found between brain neurotransmitter levels, the hyperactivity phenotype, Pls level and the severity of Pex7 genotype. In conclusion, our study showed evidence of a genotype-phenotype correlation between the severity of Pex7 deficiency and several clinical and neurobiochemical phenotypes in RCDP1 mouse models. We propose that PA accumulation may underlie the cerebellar atrophy seen in older RCDP1 patients, as even relatively low tissue levels were strongly associated with Purkinje cells loss over time in the murine models. Also, our data demonstrate the interrelation between Pls, brain neurotransmitter deficiencies and the neurobehavioral phenotype, which could be further used as a valuable clinical endpoint for therapeutic interventions. Finally, these models show that incremental increases in Pex7 levels result in dramatic improvements in phenotype.